Auditory feedback of one’s own voice is used for high-level semantic monitoring: the “self-comprehension” hypothesis - Lind, Andreas; Hall, Lars; Breidegard, Björn; Balkenius, Christian; Johansson, Petter (Frontiers in Human Neuroscience, 2014)
What would it be like if we said one thing, and heard ourselves saying something else? Would we notice something was wrong? Or would we believe we said the thing we heard? Is feedback of our own speech only used to detect errors, or does it also help to specify the meaning of what we say? Comparator models of self-monitoring favor the first alternative, and hold that our sense of agency is given by the comparison between intentions and outcomes, while inferential models argue that agency is a more fluent construct, dependent on contextual inferences about the most likely cause of an action. In this paper, we present a theory about the use of feedback during speech. Specifically, we discuss inferential models of speech production that question the standard comparator assumption that the meaning of our utterances is fully specified before articulation. We then argue that auditory feedback provides speakers with a channel for high-level, semantic “self-comprehension”. In support of this we discuss results using a method we recently developed called Real-time Speech Exchange (RSE). In our first study using RSE (Lind et al, submitted) participants were fitted with headsets and performed a computerized Stroop task. We surreptitiously recorded words they said, and later in the test we played them back at the exact same time that the participants uttered something else, while blocking the actual feedback of their voice. Thus, participants said one thing, but heard themselves saying something else. The results showed that when timing conditions were ideal, more than two thirds of the manipulations went undetected. Crucially, in a large proportion of the non-detected manipulated trials, the inserted words were experienced as self-produced by the participants. This indicates that our sense of agency for speech has a strong inferential component, and that auditory feedback of our own voice acts as a pathway for semantic monitoring.